Alimentary habits of infantile Pleurodema nebulosum (Anura: Leptodactylidae), in Matagusanos, San Juan, Argentina - Sanabria, Eduardo (2007)
The alimentary habits of Pleurodema nebulosum in the west of Argentina are unknown. The objective in this work was to analyze the diet of a population of infantile of P. nebulosum. We analyze 34 stomachs, the preys were classified and measured (wide and long), and their volumes were estimated with the sphere ellipsoid. It was considered the occurrence frequency and the abundance. The IRI most important were: Hemiptera (1867), Hymenoptera (1431), Coleoptera (127), among others. The preys with highest presence were the Hymenoptera (48,5%), Hemiptera (26,9%) y Coleoptera (10,8%). The value of mean diversity was of 0,19 (SD= 0,2) and the width of trophic niche was of 3,17; it could be indicate a possible specialization. But, in considering the low diversity values, it could be for the scarce readiness of preys in that moment too.